Analisis pemikiran K. H. Ahmad Bahauddin Nursalim (Gus Baha’) dalam menghadapi pola pikir Gen-Z di era modern - Mahmudah, Ni'matul (Maliki Interdisciplinary Journal, 2024)
In the modern era, amidst the turmoil of social and technological change shown by the mindset of Z-Generation (Gen-Z), the views of K.H. Ahmad Bahauddin Nursalim or who is familiarly called Gus Baha' is able to show his potential as a valuable guide in people's lives. This study analyzes Gus Baha’s approach to responding to Gen-Z dynamics. Through qualitative analysis, the findings show that this approach combines his thoughts as a salaf scholar who adapts to the complexities of the contemporary world. Gus Baha’ encourages intergenerational dialogue and contextual education as a way to develop a balanced mindset. Self-awareness and moral leadership are also emphasized in maintaining ethics in the digital world. This view provides a foundation for facing the challenges of the Gen-Z mindset in the modern era with an inclusive, educative, and morality approach as the central points. So, this research will provide an overview of Gus Baha''s thoughts which provide a strong foundation for the Gen-Z mindset in the modern era, so that his thoughts can be relevant and implemented in today's life.